2018
DOI: 10.1021/acssuschemeng.8b02686
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Reactive Distillation Process for the Sustainable Synthesis of Natural Benzaldehyde

Abstract: Benzaldehyde (BA) is an aromatic flavor compound with a distinctive bitter almond taste and odor, being the second most produced and valuable natural fruit flavor (after vanillin). Compared to the chemical synthesis route, the BA production from natural resources is very expensive hence significant research effort has spurred into finding more feasible solutions. This study presents a novel reactive distillation (RD) process for the synthesis of natural BA by the alkaline hydrolysis reaction of cinnamaldehyde … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…The foremost challenge among the eight is to develop cost-effective and energy-efficient alternatives of distillation. In the advancement toward developing efficient separation processes, it is vital to understand and explore the fundamental molecular, chemical, and physical properties of chemicals. …”
Section: Introductionmentioning
confidence: 99%
“…The foremost challenge among the eight is to develop cost-effective and energy-efficient alternatives of distillation. In the advancement toward developing efficient separation processes, it is vital to understand and explore the fundamental molecular, chemical, and physical properties of chemicals. …”
Section: Introductionmentioning
confidence: 99%
“…The maximum conversion was obtained was 70 % in 4 h with 100 % selectivity towards natural benzaldehyde in the optimum conditions of the reaction. Hong Li et al [6] studied the synthesis of natural benzaldehyde by the alkaline hydrolysis reaction of cinnamaldehyde using β-cyclodextrin as a phase transfer catalyst in the batch reactive distillation. The paper reported that the conversion and the yield of benzaldehyde can be achieved higher with shorter residence time than for traditional process.…”
Section: Introductionmentioning
confidence: 99%
“…The main research and development (R&D) steps that are used to develop a RD process are illustrated in Figure 2. 8 Literature data and rigorous simulations are typically used to guide the conceptual process design and the experimental program, while the lab/pilot-scale experiments serve to validate the simulation model. Afterwards, the experimentally validated model is used for process scale-up, sensitivity studies, optimization, and economic evaluation.…”
Section: Introductionmentioning
confidence: 99%